Data to model the effect of Inventory turnover Efficiency on Automobile firm’s Profitability and Enterprise value: A partial least squares structural equation modeling approach (PLS-SEM) - NAIDU, M.PURUSHOTTAM; KASTHURI, G.V.K. (The journal of contemporary issues in business and government, 2021)
Purpose: Inventory turnover or efficiency an essential element in the automobile industry. This study aimed to identify paths and model fit for cash profitability and enterprise value due to the inventory turnover ratio using partial least square structural equation modeling (PLS-SEM). Methods: sample includes 8 active Indian automobile companies (2-3 Wheeler) listed and traded on BSE (Bombay stock exchange). The present study covers consolidation financial statements for a period of 10 years (2010-20120). A conceptual structural model was developed for testing six hypotheses. H1: What was the effect of the inventory turnover ratio on operating profit per share?; H2: What was the effect of inventory turnover ratio on return on assets ?; H3: What was the effect of return on assets on cash earnings per share ?; H4: What was the effect of operating profit margin per share on cash earnings per share?; H5: What was the effect of inventory turnover ratio on enterprise value ?; H6: What was the effect of operating profit per share on enterprise value ?. Results: 75 samples in the study, using structural equation modeling all effect size, collinearity (inner) issues, predictive accuracy was confirmed. All path coefficients were positive and statistically significant(H1:ß = 0.854, P < 0.001; H2: ß = 0.703, P < 0.001; H3:ß = 0.161, P < 0.001; H4 :ß = 0.856, P < 0.001: H5 :ß = 0.428, P < 0.001: H6 : ß = 0.502, P < 0.001).The in- sample predictive power was substantial for cash earnings per share (R2=0.939), earnings before interest tax per share (R2=0.729), enterprise value (R2=0.803), and moderate for return on assets(R2=0.494). Overall model fit is established (SRMR<0.021 at 95% & 99%). Originality: This article provides how operating efficiency influences enterprise value and cash profitability for the investors of 2-3 wheeler automobile firms. This result supports management performance towards operating efficiency that creates both profit and enterprise value.